Efektivitas latihan alternate leg bounding terhadap keterampilan menendang pada atlet taekwondo - Rusli, Muhammad; Jud, Jud; Suhartiwi, Suhartiwi; Marsuna, Marsuna; Nuharti, Nuharti (Universitas Nusantara PGRI Kediri, 2024)
Taekwondo emphasizes kicking techniques, including elgol dollyo chagi, a spinning head kick requiring flexibility, strength, speed, coordination, and precision for optimal effectiveness. This study aims to evaluate the effectiveness of alternate leg bounding training on the elgol dollyo chagi performance of taekwondo athletes. It employs experimental research with a one-group pretest-posttest design. The participants consisted of 30 taekwondo athletes selected through total sampling, meaning the entire population was used as the sample. The research instrument involves an elgol dollyo chagi performance test conducted over a duration of 30 seconds. Data analysis uses descriptive tests, and the analysis prerequisite tests with data normality and data homogeneity, and continued with hypothesis testing using the t-test with the spss program version 23. The results of the t-test value obtained were 15.455, with a pretest mean of 23.83 and a posttest mean value of 36.20. Based on these results, the p-value is greater than 0.05 and has an increase of 12.37%. The results of the study showed a significant increase in the speed of execution of the elgol dollyo chagi kick after following the alternate leg bounding training program. In addition, this research is also useful in terms of athlete physical development, including strength, agility, coordination, and injury prevention.